What Five 9's Really Means and Managing Expectations - Arno, R.; Gross, P.; Schuerger, R. (Conference Record of the 2006 IEEE Industry Applications Conference Forty-First IAS Annual Meeting, 2006)
When the concept of reliability began to formally become an integrated engineering approach in the 50's, reliability was associated with failure rate. Today the term "reliability" is used as an umbrella definition covering a variety of subjects including availability, durability, quality and sometimes the function of the product. Currently in the power industry, when the subject is reliability, it is very common to see statements about "five 9's". The implication is that this term some how defines a specific level of reliability. The reality is that it is only one component of reliability and must be used in its intended manor. This paper presents the industry accepted definitions along with examples to show what "five 9's" really means in specific instances and with specific electrical distribution systems. The issue to address is that "reliability" is a term with a specific definition (given below) and the "five 9's" refers to "availability"; it means an availability of 0.99999. As shown, it requires more than a single term to adequately define the expectations for reliable operation of critical facilities